ConGen—A Simulator-Agnostic Visual Language for Definition and Generation of Connectivity in Large and Multiscale Neural Networks - Herbers, Patrick; Calvo, Iago; Diaz-Pier, Sandra; Robles, Oscar D.; Mata, Susana; Toharia, Pablo; Pastor, Luis; Peyser, Alexander; Morrison, Abigail; Klijn, Wouter (Frontiers in Neuroinformatics, 2022)
An open challenge on the road to unraveling the brain's multilevel organization is establishing techniques to research connectivity and dynamics at different scales in time and and space, as well as the links between them. This work focuses on the design of a framework that facilitates the generation of multiscale connectivity in large neural networks using a symbolic visual language capable of representing the model at different structural levels -- ConGen. This symbolic language allows researchers to create and visually analyze the generated networks independently of the simulator to be used, since the visual model is translated into a simulator-independent language. The simplicity of the front-end visual representation, together with the simulator independence provided by the back-end translation, combine into a framework to enhance collaboration among scientists with expertise at different scales of abstraction and from different fields. On the basis of two use cases, we introduce the features and possibilities of our proposed visual language and associated workflow. We demonstrate that ConGen enables the creation, editing and visualization of multiscale biological neural networks and provides a whole workflow to produce simulation scripts from the visual representation of the model.